2019
DOI: 10.3390/cancers12010054
|View full text |Cite
|
Sign up to set email alerts
|

DCLK1 Monoclonal Antibody-Based CAR-T Cells as a Novel Treatment Strategy against Human Colorectal Cancers

Abstract: CAR-T (chimeric antigen receptor T cells) immunotherapy is effective in many hematological cancers; however, efficacy in solid tumors is disappointing. Doublecortin-like kinase 1 (DCLK1) labels tumor stem cells (TSCs) in genetic mouse models of colorectal cancer (CRC). Here, we describe a novel CAR-T targeting DCLK1 (CBT-511; with our proprietary DCLK1 single-chain antibody variable fragment) as a treatment strategy to eradicate CRC TSCs. The cell surface expression of DCLK1 and cytotoxicity of CBT-511 were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…According to previous evidence, raised levels of Doublecortin-like kinase 1 (DCLK1) expression in human colorectal tumors are associated with higher mortality rates. A recent report revealed that DCLK1’s targeted CAR-T therapy effectively eradicates primary and metastatic colon cancer cells [ 105 ].…”
Section: Car T Cell Therapy In Solid Tumors: Recent Advancesmentioning
confidence: 99%
“…According to previous evidence, raised levels of Doublecortin-like kinase 1 (DCLK1) expression in human colorectal tumors are associated with higher mortality rates. A recent report revealed that DCLK1’s targeted CAR-T therapy effectively eradicates primary and metastatic colon cancer cells [ 105 ].…”
Section: Car T Cell Therapy In Solid Tumors: Recent Advancesmentioning
confidence: 99%
“…A further study using anti-EpCAM CAR T cells for local treatment of peritoneal carcinomatosis in xenograft mice demonstrated the efficacy of this approach for the treatment of gastrointestinal and gynecologic malignancies [ 105 ]. Numerous preclinical studies have indicated other surface markers potentially useful to identify or target CSCs: CD90, ALDH, CD47, CD44, CD24, microtubule-associated doublecortin-like kinase 1 (DCLK1) that are expressed in multiple cancer types with a higher expression in CSCs compared to other bulk tumor cells [ 82 , 97 , 106 , 107 ]. DCLK1 has been described as a CSC associated antigen in colon, pancreatic [ 108 , 109 , 110 ] and even in Cholangiocarcinoma (CCA) tumors [ 111 ].…”
Section: Cellular Immunotherapy Targeting Cscsmentioning
confidence: 99%
“…Utilizing well-characterized CSC markers makes it possible to develop CAR-T cells with the potential to eliminate CSCs. As a CAR-T target, DCLK1 single-chain antibody variable fragment (CBT-511), showed a prominent cytotoxic effect against tumor cells and reduced tumor growth in CRC [ 27 ]. CBT-511 also increased IFN-γ release in CRC cells (2D and 3D).…”
Section: Development Of Dclk1-targeted Therapeutic Agents and Biolmentioning
confidence: 99%
“…Furthermore, several recent studies show that DCLK1 affects tumor growth and metastasis via regulating TAM and immune checkpoint. Finally, monoclonal antibodies and chimeric antigen receptor T-Cells (CAR-T) based on DCLK1 have demonstrated potential as novel cancer immunotherapies [ 26 , 27 , 28 ]. Herein we review key advances in the understanding of DCLK1 and DCLK1+ TCs function in the context of the tumor and immune microenvironment and discuss future directions for DCLK1-based research and development.…”
Section: Introductionmentioning
confidence: 99%